Mapping of MPH programs in terms of geographic distribution across various universities and institutes of India-A desk research - Pooja S. Dhagavkar; Mubashir Angolkar; Jyoti Nagmoti; Sanjay Zodpey (Frontiers Media S.A., 2024)
BackgroundLandscaping studies related to public health education in India do not exclusively focus on the most common Masters of Public Health (MPH) program. The field of public health faces challenges due to the absence of a professional council, resulting in fragmented documentation of these programs. This study was undertaken to map all MPH programs offered across various institutes in India in terms of their geographic distribution, accreditation status, and administration patterns.MethodologyAn exhaustive internet search using various keywords was conducted to identify all MPH programs offered in India. Websites were explored for their details. A data extraction tool was developed for recording demographic and other data. Information was extracted from these websites as per the tool and collated in a matrix. Geographic coordinates obtained from Google Maps, and QGIS software facilitated map generation.ResultsThe search identified 116 general and 13 MPH programs with specializations offered by different universities and institutes across India. India is divided into six zones, and the distribution of MPH programs in these zones is as follows, central zone has 20 programs; the east zone has 11; the north zone has 35; the north-east zone has 07; the south zone has 26; and the west zone has 17 MPH programs. While 107 are university grants commission (UGC) approved universities and institutes, only 46 MPH programs are conducted by both UGC approved and National Assessment and Accreditation Council (NAAC) accredited universities and institutes. Five universities are categorized as central universities; 22 are deemed universities; 51 are private universities; and 29 are state universities. Nine are considered institutions of national importance by the UGC, and four institutions are recognized as institutions of eminence. All general MPH programs span 2 years and are administered under various faculties, with only 27 programs being conducted within dedicated schools or centers of public health.ConclusionThe MPH programs in India show considerable diversity in their geographic distribution, accreditation status, and administration pattern.